Trends in dermoscopy use in the UK: results from surveys in 2003 and 2012 - Thomas D. Butler (Mattioli1885, 2015)
Background: Dermoscopy is a useful tool to aid diagnosis of pigmented and non-pigmented skin lesions, as well as many other dermatological conditions. Use of dermoscopy is increasing worldwide, but to date, there are no reported data on attitudes of dermatologists in the United Kingdom (UK) towards dermoscopy.